Semiotika Dalam Film Waktu Maghrib 2 Karya Sidharta Τατα - Siti Soleha; Desty Endrawati Subroto; Mahpudoh Mahpudoh (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to describe the denotative, connotative, and mythical meanings in Sidharta Tata's film Waktu Maghrib 2 using Roland Barthes's semiotic theory. This study employed a qualitative descriptive method, with data collection techniques consisting of observing and taking notes on scenes, dialogue, and visual and audio elements in the film. The results show that Waktu Maghrib 2 contains various signs that represent the religious, social, and cultural values ​​of the community. The denotative meaning is seen in the depiction of events in the film, the connotative meaning conveys moral and religious messages, while the mythical meaning represents the community's beliefs about the time of Maghrib. This study concludes that Waktu Maghrib 2 functions not only as a medium of entertainment but also as a medium for conveying moral, cultural, and religious messages.